Contribución del turismo gastronómico en el logro de los objetivos del desarrollo sostenible 8, 12, 14 en el cantón Buena Fe, año 2022 - Saltos Zamora, María Elizabeth (2022)
This research work seeks to analyze the impact that gastronomic tourism has had to generate a benefit in achieving the objectives of sustainable development, where it has improved practices in both production and consumption in the locality. In recent years, the canton of Buena Fe has made great progress in generating the necessary resources to encourage tourism, both in tourist attractions and gastronomic tourism sites, where businesses have been a fundamental pillar to promote post-pandemic economic recovery. Within the research, the identification of the places with greater influence within the gastronomic tourism within the Buena Fé canton was carried out, among the main ones that are detailed within the research such as Los girasoles, Coco Beach, Asadero "Todos Vuelven", among others. In addition, a detail was made of the impacts that tourism has had within the Buena Fé canton in the social, economic and environmental aspects, where in the generation of sources of employment and that the price of inputs directly influences the quality of the food offered, giving it a rating of 5 on the Likert scale used. Subsequently, with these data, the respective conclusions were drawn, where the objectives of the research were verified.